2019
DOI: 10.1002/jcb.28495
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications but not genetic polymorphisms regulate KEAP1 expression in colorectal cancer

Abstract: Kelch-like ECH-associated protein 1 (KEAP1), as a negative regulator of nuclear factor erythroid 2 like 2 (NRF2), plays a pivotal role in NRF2 signaling pathway and involves in tumorigenesis. Polymorphisms and methylation in gene promoter region may influence its expression and be related to cancer susceptibility. In this study, we examined the effect of the KEAP1-NRF2 interaction on the risk of colorectal cancer (CRC). The polymorphisms of NRF2 and KEAP1 were genotyped using the improved multiplex ligase dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…Hypermethylation of these CpG sites markedly lowered NRF2 expression in prostate tumorigenesis [32]. As discussed above, KEAP1 promoter methylation was first reported in lung cancer, but similar observations have been linked to poor prognosis in glioma, breast cancer, non-small cell lung carcinoma, colorectal cancer, clear renal cell carcinoma, and pancreatic cancer [33][34][35][36][37][38].…”
Section: Dna Methylationmentioning
confidence: 71%
“…Hypermethylation of these CpG sites markedly lowered NRF2 expression in prostate tumorigenesis [32]. As discussed above, KEAP1 promoter methylation was first reported in lung cancer, but similar observations have been linked to poor prognosis in glioma, breast cancer, non-small cell lung carcinoma, colorectal cancer, clear renal cell carcinoma, and pancreatic cancer [33][34][35][36][37][38].…”
Section: Dna Methylationmentioning
confidence: 71%
“…Aberrant hypermethylation in KEAP1 promoter region was the most common alteration found in nearly half of the non-small cell lung cancer (NSCLC) cases ( Muscarella et al, 2011a ), and has been proven to be associated with poor prognosis in various cancers including malignant glioma, breast cancer and pancreatic cancer ( Muscarella et al, 2011b ; Barbano et al, 2013b ; Zhang et al, 2016b ). Numbers of research has revealed that 5-aza-2′-deoxycytidine (5-aza) treatment demethylated the CpG sites in the KEAP1 promoter region, synergistically contributing to KEAP1 overexpression, NRF2 degradation and inactivation of various relevant signal pathways ( Wang et al, 2008b ; Guo et al, 2015c ; Gao et al, 2019 ), which were related to enhanced survival and reduced lymph node metastasis of NSCLC patients ( Chien et al, 2015 ). Contrary to 5-aza, Fumonisin B, a common toxic mycotoxins of cereal grains, activated NRF2/KEAP1 pathway by hypermethylating CpG islands in KEAP1 gene, consequently enhancing ROS production along with promoting cell membrane damage in human hepatoma cells ( Arumugam et al, 2021 ).…”
Section: Therapeutic Strategies Targeting Epigenetic Modifications Of...mentioning
confidence: 99%
“…Transcription factor NFE2L2 (nuclear factor, erythroid 2 like 2), also named NRF2, functions as an oncogene or tumor suppressor, it regulates the cellular antioxidant response and promotes cancer chemotherapy resistance, metastasis, and progression [26][27][28]. The rs6706649 and rs6721961 in NFE2L2 may influence breast cancer prognosis, rs6721961 and rs35652124 are associated with susceptibility to colorectal cancer [29,30].…”
Section: Ivyspring International Publishermentioning
confidence: 99%